Apoyo en los procesos de diseño y construcción en la empresa Construimos Asociados de la ciudad de Duitama-Boyacá. - Escobar Silva, Paula Andrea (Universidad Antonio Nariño, 2022)
This document deals with key aspects learned and practiced during the internship carried out at Construimos Asociados company located in the city of Duitama, it provides the necessary processes for structural design support and review., soil studies, subdivisions, designs of hydr osanitary networks, architectural designs, issuance of licenses in urban curatorship, drafting of construction contracts, among others. All of this being of great benefit for working life as engineers, strengthening also other areas such as labor relation s, functions in companies, teamwork and many others that will be of vital importance in both work and personal life.